1993
DOI: 10.1007/bf02098460
|View full text |Cite
|
Sign up to set email alerts
|

Detection in an enzyme immunoassay of an immune response to a recombinant fragment of the 128 kilodalton protein (CagA) ofHelicobacter pylori

Abstract: The possibility of using a recombinant fragment of the CagA (128 kDa protein) for the diagnosis of Helicobacter pylori infection was evaluated. Following cloning of the gene coding for the CagA, a recombinant fragment of it was expressed in Escherichia coli, purified and used in Western blot and an EIA to screen sera from 82 patients with gastroduodenal disease who underwent endoscopic examination. In Western blot, good correlation was found between the serological data obtained with the recombinant antigen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
81
2
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 28 publications
4
81
2
1
Order By: Relevance
“…Detection of antibodies against HP-NAP in serum by ELISA Recombinant HP-NAP was prepared and purified, and ELISA was carried out as previously described [24][25][26][27] . Briefly, immunoplates (Nunc, Denmark) were coated with rNAP (5µg/well) and incubated overnight at 4℃.…”
Section: Screening For Seropositive Individuals With Igg Antibodies Amentioning
confidence: 99%
“…Detection of antibodies against HP-NAP in serum by ELISA Recombinant HP-NAP was prepared and purified, and ELISA was carried out as previously described [24][25][26][27] . Briefly, immunoplates (Nunc, Denmark) were coated with rNAP (5µg/well) and incubated overnight at 4℃.…”
Section: Screening For Seropositive Individuals With Igg Antibodies Amentioning
confidence: 99%
“…Epidemiological and serological studies have revealed that H. pylori strains containing the CagA protein are associated with more severe disease (2) and harbor a 40-kb pathogenicity island (PAI) (3,4). The PAI encodes a bacterial type IV secretory system that secretes and translocates the CagA protein into host cells (5)(6)(7)(8), where it is phosphorylated by a host-cell kinase and causes morphological changes (7).…”
mentioning
confidence: 99%
“…The toxin was named vacuolating cytotoxin (VacA) because it induces vacuolation of cultured mammalian cells (11,12). Toxigenic strains of H. pylori are frequently cultured from biopsies of gastroduodenal ulcers (9,(13)(14)(15), whereas H. pylori strains harboring an altered VacA toxin gene are noncytotoxic (13)(14)(15)(16)(17)(18). Oral administration of purified VacA to mice induces gastric mucosa degeneration and inflammatory cell recruitment, characteristic of H. pylori-mediated diseases (20,21).…”
mentioning
confidence: 99%